Peran LSM dalam Mendukung Kebijakan Pengarusutamaan Gender pada Kegiatan Pengelolaan Sumberdaya Alam (Studi Kasus Pada LSM RMI Bogor) - Nurmelati Septiana (Universitas Lambung Mangkurat, 2011)
This research aim is to describe the role of NGOs in supporting the Gender Mainstreaming policy in natural resource management activities. It is a qualitative study by using the Focus Group Discussion (FGD) technique in data collection. Data analysis was performed descriptively based on document analysis, qualitative data and focus group interviews. This study shows that the success of the Gender Mainstreaming policy is inseparable from the active collaboration with NGOs who engaged in natural preservation. RMI Bogor, since the beginning of the program, has focused on community development activities that were responsive to gender, i.e: involving both men and women as the target of their activities. In RMI Bogor’s work programs, gender issues in natural resource management are already a practical dimension which is implemented on their work programs and community assistances.